Intergovernmental Relations in the Educational Management System of Rural Preschool in China：Policy Evolution and Future Development. Issue 1 (4th March 2021) - Li, Lin; Sha, Li; Fang, Junjun; Xiong, Cancan
Abstract: Intergovernmental Relations are conventionally defined as important interactions between governmental units of all types and levels. In the process of universalization of rural preschool education, intergovernmental relations act as an increasingly significant role in facilitating the operating mechanism of vertical institutions at national, provincial, and local levels. This study investigated the policy evolution of intergovernmental relations in the rural preschool educational management system since the founding of the People's Republic of China. It reveals the developmental tendency of government accountabilities "from involvement to withdrawal and finally to leading", the focus of government responsibilities "from grassroots institutes to higher-level governments". The study also explores the influencing mechanisms that affect profound changes in the intergovernmental relations of rural preschool education, and proposes principles of "dominant role of governments, responsibilities heterogeneous at different levels, and appropriate match between administrative power and financial power" to further promote the reform of educational management system in a systematic and sustainable way.